(untitled) (Research, Society and Development, 2020)
The present study aimed to characterize common bean cultivars (Phaseolus vulgaris L.) in the Aquidauana-MS region based on the DHE test (Distinction, Homogeneity and Stability). The experiment was carried out at the State University of Mato Grosso do Sul. The design used was completely randomized blocks, with four replications, each containing a sample consisting of 25 seeds. Ten common bean cultivars were used, BRS Radiante, Pérola, Madre Pérola, BRS Estilo, BRS Esplendor, Jalo Precoce, BRS Campeiro, BRS Amethyst, BRSMG Highce and BRS Pitanga. The characterization of the genotypes was based on the morphological descriptors for the crop, standardized according to the Minimum Descriptors to Characterize Common Bean Cultivars / Varieties. To describe the qualitative factors, we used: Ribs in the seed, absent or present; Seed color, uniform or uneven; Seed halo, absent or present; Seed halo color, same seed color or different from seed; Commercial Group to which it belongs, white, carioca, jalo, mulatinho, black, rosinha, purple or special; Seed shape, spherical; elliptical: oblong / short reniform; medium oblong / reniform; long oblong / reniform; Flatness degree, flattened; semi-full; full. While the quantitative descriptors were measured with the aid of a caliper and an analytical digital scale, being evaluated: mass of one hundred grains (g), with average humidity between 12 to 14%; seed length, width and thickness (mm). The use of qualitative or quantitative descriptors considerably modifies the grouping of common bean genotypes, the Gower algorithm being effective in grouping common bean genotypes based on the descriptors.